2002
DOI: 10.1046/j.1360-0443.2002.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

The second National Epidemiological Survey on illicit drug use at six high‐prevalence areas in China: prevalence rates and use patterns

Abstract: Compared with the data from the 1993 survey, illicit drug use has continued to escalate across the areas, calling for priority concern in various sections of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…The specifics of China's drug problem have been thoroughly documented by Hao et al who described the prevalence and patterns of illicit drug use in the heavily populated areas of Yunnan, Sichuan, Gansu, and Gungdong provinces between 1993 and 2000 (Hao et al 1998(Hao et al , 2002Wolf et al 2004). Hao and colleagues screened more than 50,000 individuals aged 15 or above in these communities and interviewed possible abusers.…”
Section: The Present Epidemic Of Drug Abuse In China (From the 1980s mentioning
confidence: 98%
“…The specifics of China's drug problem have been thoroughly documented by Hao et al who described the prevalence and patterns of illicit drug use in the heavily populated areas of Yunnan, Sichuan, Gansu, and Gungdong provinces between 1993 and 2000 (Hao et al 1998(Hao et al , 2002Wolf et al 2004). Hao and colleagues screened more than 50,000 individuals aged 15 or above in these communities and interviewed possible abusers.…”
Section: The Present Epidemic Of Drug Abuse In China (From the 1980s mentioning
confidence: 98%
“…Although the rate of schizophrenia is relatively stable, a substantial increase in substance problems has been observed in the last three decades in China [48]. The rate of alcohol and substance abuse in China, despite the recent increase, remains much lower than in the West.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in other countries have revealed huge differences in 2-year prevalence of illicit drug use. The UK National Survey suggest prevalences of between 32 and 37% for males aged 16-24 and of between 22 and 29% for females of the same age group [9], whereas a National Survey in China found a prevalence of 1.2% among those aged 15 or above, 1.8% in males and 0.5% in females [15], with opiates being the main drugs used. Discussion of these huge differences in prevalence across countries needs to be taken with caution and is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%